PIPER adult comfort: an open-source full body human body model for seating comfort assessment and its validation under static loading conditions - Liu, Shenghui; Beillas, Philippe; Ding, Li; Wang, Xuguang (Frontiers in Bioengineering and Biotechnology, 2023)
Today, people spend more and more time seated in transportation, at home, and in the office. Sustained loads on the soft tissue of the buttocks during long sitting periods may cause seating discomfort or even pressure ulcers for wheelchair users. In addition to the pressure distributions, soft tissue deformations and internal loading (in terms of compression or strain) are generally considered relevant for seating discomfort assessment. However, internal biomechanical parameters cannot be easily measured in vivo. With the development of computational capability, many finite element (FE) human body models (HBM) were developed to assess seating discomfort or pressure ulcer risk based on predicted internal biomechanical parameters. However, their validations were performed mainly against pressure-related parameters under either very simplified conditions or a specific seat condition. In the real world, seat configurations vary, and different seat configurations need to be designed. Prior to using the HBM in virtual seat design, its validation should cover a large range of seats used in daily life. In this paper, we introduce an adult-sized FE full-body HBM for seating comfort assessments and present its validation in different static seating conditions in terms of pressure distribution and contact forces. Soft tissue deformations under the ischial tuberosity are also verified against data from an MRI study. The model will be published openly online as part of the PIPER open-source project (www.PIPER-project.org) to facilitate its reuse and improvement.